2008
DOI: 10.1038/ijo.2008.218
|View full text |Cite
|
Sign up to set email alerts
|

Higher body fat percentage is associated with increased cortisol reactivity and impaired cognitive resilience in response to acute emotional stress

Abstract: Objective: Cortisol is elevated in individuals with both increased emotional stress and higher percentages of body fat. Cortisol is also known to affect cognitive performance, particularly spatial processing and working memory. We hypothesized that increased body fat might therefore be associated with decreased performance on a spatial processing task, in response to an acute real-world stressor. Design: We tested two separate samples of participants undergoing their first (tandem) skydive. In the first sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 42 publications
6
25
1
3
Order By: Relevance
“…These findings align with previous observations that skydiving increases cortisol levels in both experienced [15], and novice [7,8,9] skydivers. However, our study is the first to directly compare cortisol reactivity to skydiving in novice versus experienced skydivers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings align with previous observations that skydiving increases cortisol levels in both experienced [15], and novice [7,8,9] skydivers. However, our study is the first to directly compare cortisol reactivity to skydiving in novice versus experienced skydivers.…”
Section: Discussionsupporting
confidence: 92%
“…For example, skydiving leads to activation of both the SAM and HPA axis, as evidenced by post-jump increases in the SAM axis biomarker salivary  amylase and cortisol respectively in novice jumpers [7,8]. Similarly, other factors which are associated with activation of the SAM axis, such as increased heat rate [9,10] and symptoms of hyperarousal, (e.g. heart racing, sweating, shaking/trembling and shortness of breath) [11], have been observed in individuals undertaking their first skydive.…”
Section: Introductionmentioning
confidence: 99%
“…Combining Cort, A-A changes and GSR data with SA scores, a significant association between A-A levels, GSR values and SA, but not CA scores emerged. Research points to cortisol reactivity as the mechanism for observed cognitive stress vulnerability [51]. However, our data do not support this hypothesis.…”
Section: Discussioncontrasting
confidence: 99%
“…Few studies have examined both hormonal and autonomic responses throughout the course of a parachute jumping event and the state anxiety associated with such a performance [19,51]. A similar lack of information exists as to somatic and cognitive anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Habituation results, however, were ambivalent, since the CORT response patterns were scattered. Finally, MujicaParodi, Renelique and Taylor (2008) examined tandem skydivers for CORT, cardiac variables, and diverse cognitive performance outcomes. They found increased CORT reactivity and an overall cognitive decline that, notably, were positively correlated with a greater body fat percentage.…”
Section: Introductionmentioning
confidence: 99%